Ethical Challenges of Islam in the Digitalisation of Sharia Banking Services - Rindu Oktavia (Journal of Islamic Digital Economic and Finance, 2025)
Introduction: The digitisation of Islamic banking services is growing rapidly in line with technological advances and changes in customer behaviour. Digital transformation provides convenience, efficiency, and expanded access to Islamic financial services. However, digitisation also presents various ethical challenges, particularly in relation to compliance with Islamic principles such as fairness, transparency, data protection, and trustworthiness in the management of banking services. Objective: This study aims to examine the Islamic ethical challenges that arise in the process of digitising Islamic banking services and to analyse the application of Islamic ethical values in the operation of digital-based banking services. Method: This study uses a descriptive qualitative approach through a literature review. Data were obtained from scientific journals, books, regulatory documents, and reports on Islamic ethics and the digitalisation of Islamic banking. Data were analyzed using thematic analysis to identify the main ethical issues relevant to this study. Result: The study finds that the main ethical challenges in the digitalisation of Islamic banking include maintaining Sharia compliance in digital and automated systems, protecting customer data and privacy, ensuring transparency in digital transactions, and balancing technological efficiency with ethical accountability. The limitations of the ethical governance framework and the low level of digital literacy among some stakeholders further exacerbate these challenges. Implication: This study emphasises the importance of strengthening Sharia-based ethical governance, developing digital guidelines aligned with Islamic principles, and maintaining continuous oversight of the digitalisation process. These efforts are necessary to maintain public trust and ensure the sustainability of Islamic banking in the digital era